Shear Stress Induced by an Interstitial Level of Slow Flow Increases the Osteogenic Differentiation of Mesenchymal Stem Cells through TAZ Activation - Kim, Kyung Min (Public Library of Science, 2014)
Shear stress activates cellular signaling involved in cellular proliferation, differentiation, and migration. However, the mechanisms of mesenchymal stem cell (MSC) differentiation under interstitial flow are not fully understood. Here, we show the increased osteogenic differentiation of MSCs under exposure to constant, extremely low shear stress created by osmotic pressure-induced flow in a microfluidic chip. The interstitial level of shear stress in the proposed microfluidic system stimulated nuclear localization of TAZ (transcriptional coactivator with PDZ-binding motif), a transcriptional modulator of MSCs, activated TAZ target genes such as CTGF and Cyr61, and induced osteogenic differentiation. TAZ-depleted cells showed defects in shear stress-induced osteogenic differentiation. In shear stress induced cellular signaling, Rho signaling pathway was important forthe nuclear localization of TAZ. Taken together, these results suggest that TAZ is an important mediator of interstitial flow-driven shear stress signaling in osteoblast differentiation of MSCs.